Comparative analysis of the transcriptome of Bacillus subtilis natto incubated in different substrates for nattokinase production. (June 2023) - Liu, Dandan; Han, Zhenxing; Hu, Ziwei; Yu, Chenrui; Wang, Yu; Tong, Jie; Fang, Xu; Yue, Wenjin; Nie, Guangjun
Abstract: Nattokinase (NK) is a serine protease to prevent and treat cardiovascular diseases, and owns potential applications in the fields of food and medicine. However, the unclear correlationship of NK synthesis with substrate metabolism prevents from improving NK production of Bacillus subtilis natto ( B. natto). To reveal the effects of various substrates on NK synthesis, soybean (SB), sunflower seed kernel (SF) and Lycium barbarum (LB) as incubation media were compared in NK yield in this work. The results indicated that SB achieved the most NK yield of 9582 FU/mL, followed by 7466 FU/mL of SF and 0 FU/mL of LB. It is revealed from the transcriptome analysis that the media with high level of protein promote the conversion of various amino acids into other proteins through glycolysis and tricarboxylic acid cycle, and into sugar through gluconeogenesis, enhancing the signal of cell density to initiate the transcription of aprE . However, the polysaccharides in LB cannot provide sufficient nitrogen, leading to amino acid starvation to repress NK synthesis. These findings will improve NK production of B. natto in the optimization of culture medium, regulation of aprE expression, construction of genetically engineered bacteria, etc. Graphical Abstract: ga1 Highlights: 9582 FU/mL nattokinase was synthesized with soybean but no NK with Lycium barbarum . Proteins initiate the expression of aprE through increasing cell density. Sugars repress the transcription of aprE by reducing cell density.